Oblique cross-section nanoindentation for determining the hardness change in ion-irradiated steel. (January 2019) - Saleh, Michael; Xu, Alan; Hurt, Christopher; Ionescu, Mihail; Daniels, John; Munroe, Paul; Edwards, Lyndon; Bhattacharyya, Dhriti
Abstract: In this study, the authors have applied the "Oblique Cross Section" or OCS method, for the determination of the hardness changes in ion irradiated 316 stainless steel. The steel sample was irradiated with 1, 2 and 3 MeV He 2+ ions. The samples were then polished at an angle of ∼15° from the ion irradiated surface, and the hardness on the cross-section was tested using nanoindentation in non-continuous stiffness measurement mode (non-CSM) at various distances from the ion irradiated surface. A profile of the hardness versus depth from the irradiated surface was thus obtained. It is shown that this method is quite suitable for single energy ion irradiation, when the energy is relatively high (≥1 MeV He in stainless steel), as it gives a better match between the damage peak and hardness peak locations than the "Top-down" method. The hardness profiles can be divided into two broad regions, viz. the pre-damage-peak plateau, and the peak hardness region. The results are contrasted with finite element (FE) models. The FE modelling shows formation of a secondary plastic zone in the unirradiated material beyond the irradiated layer, which was verified by cross-sectional transmission electron microscopy (TEM). Other aspects of the deformation below the nanoindents were also studied and illuminated by cross-sectional TEM. Thus, both experimental techniques and theoretical methods are employed here to elucidate the deformation processes and hardness measurement results, thereby establishing a more profound understanding of this relatively uncommon, but potentially powerful method for testing the mechanical property changes in ion irradiated materials, and of thin-layered materials in general. Highlights: The authors used the oblique cross section (OCS) nanoindentation method for the examination of ion irradiated specimens. The OCS method allows for greater fidelity in the examination by exposing a larger cross-sectional projected area. The results show a double dished plastic zone which is confirmed numerically and experimentally through cross-sectional TEM. The results highlight the complex plastic zones formed and the strong influence of the Berkovich tip on the hardness values. The novel multiscale modelling approach, whereby the SRIM outputs are used as inputs for continuum FE models, was successful. The models were used for the prediction of the hardness increase of SS316 under He 2+ irradiation energies of 1, 2 and 3 MeV.